Formação da ligação carbono-carbono envolvendo organocalcogênios catalisada por metais de transição - Bilheri, Filipe Neimaier (2019)
In this thesis we developed a methodology for carbon-carbon bond formation via a cross-coupling reaction between classical nucleophiles and organoselenium electrophiles catalyzed by transition metals. The fact that organochalcogens could act as pseudo-halides for cross-coupling reactions makes these molecules very attractive for organic synthesis, thus providing the use of organochalcogens compounds as building blocks for the formation of different compounds. In the first part of this thesis, the coupling of several nucleophiles in sp and sp2 carbons bonded to an organoselenium species was reported. This methodology allowed to obtain alkynes and alkenes from classic coupling reactions, such as Susuki, Negishi, Kumada and Sonogashira. The products were obtained with yields from 32-95%. Subsequently, a new methodology was developed for the synthesis of indenes substituted with chalcogen atoms, through a cyclization reaction from phenylprop-2-yn-1-ol and diorgano-dichalcogens of iron catalyzed by salts. This synthesis proved to be efficient for the formation of various indenes. The products were obtained with yields from 36-76%. Thus, readily accessible substrates were used for the synthesis of disubstituted indenes with chalcogenides, forming a carbon-carbon bond and two carbon-chalcogen bonds, in the presence of a metal catalyzed process with low toxicity and low cost.